Geodiversity of the Nossa Senhora da Penha Chart, João Pessoa, Paraíba, Brazil - Pereira, Luciano Schaefer; Farias, Thiago da Silva (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2021)
This article presents the vision of geodiversity in the Nossa Senhora da Penha Chart (SB.25-Y-C-III-1-SE), scale 1: 25.000, in João Pessoa, Paraíba, in order to insert places of interest on coastal geotouristic routes. A mapping of this geodiversity and its Geoheritage was performed through the inventory of places with relevant values. It is appropriate to interconnect the coastal heritage with tourism in the area, in order to increase the interest of tourists. Geomorphologically, the terrain is divided into three large morpho-sculptural units: coastal plains, alluvial plains and tablelands, in addition to the slopes that link the tablelands with the plains. As a methodological path, a detailed study of the literature regarding the geoscientific and historical information of the area and thorough fieldwork were necessary. Seven sites were inventoried and qualitatively evaluated: Ferruginous Sandstones of Jacarapé, Altiplano Paleodunes, Urban Holocene Marine Terraces, Cabo Branco Cliff, Urban Inactive Cliff, Gramame River Mouth and Primitive Mouth of Jaguaribe River, developed at different scales. The mapped area has potential for geotourism, in connection to the geological story of the Paraiba Basin, the last part to separate from Africa during the Pangeia fragmentation, presenting geologically, geomorphologically and hydrologically valuable features.
Keywords: Geoheritage; Coastal geotourism; Geotouristic routes; Urban coast; João Pessoa